Achieving a balanced optimisation between network lifetime and data delivery latency in multihop wireless sensor networks. (5th July 2019) - Babu, Ravi; Shenoy, Udaya Kumar K.; Patil, Kiran Kumari
Data gathering using mobile sinks is considered one of the efficient and cost-effective strategies to mitigate the hotspot problem in wireless sensor networks (WSNs). Although sink mobility is beneficial in many ways, these benefits are not without its new challenges. A major concern is achieving a good balance between sensors' energy consumption and message delivery latency. The unique characteristics and requirements of wireless sensor networks make this task a significant challenge. Another major challenge is coping with the changing topology caused by the sink mobility. The sensor nodes are required to maintain fresh routes toward the latest sink location for efficient data delivery. This paper proposes data gathering schemes to address these two major issues in WSNs by using a virtual overlay structure built over the existing physical network. Simulation results reveal a reduced route reconstruction cost and a good trade-off between network life-time and data delivery latency.